Title: The Great Gatsby: A Story of The American Dream and The Social Conflict - Alaabed, Abdullah Abdulhaq Hussien (Advances in Social Sciences Research Journal, 2021)
The Great Gatsby is a novel that was written in 1925 by Scott Fitzgerald. it represents The American Dream and the desire of achieving it through the protagonist attempts to achieve The American Dream. The protagonist is Jay Gatsby he is a self-made man who belongs to the working class of society, he gained his wealth through the organized crime and illegal business, Jay was charmed by the lifestyle of the rich people and the identity of being one of them. He used his fortune to make incredible parties in his mansion showing his wealth power and to attract Daisy’s attention, the women he loves most. Gatsby represents the American dreamers who belong to the repressed class of society, this young generation who believes in The American Dream and the possibility of achieving it. The American Dream was created by the dominant class of society in order to control the economic system. The falsie fact that this dream was built upon is the social justice, the social equality that gives equal chances to everyone to achieve their desires via hard work without concern about their social background. The American Dream is mainly about either wealth obtaining which was the aspiration of these young working-class people or social ascendency. Gatsby despite his recent gained fortune and new identity as he changed his name from James to Jay Gatsby was not able to be a member of the bourgeoisies; he was rejected due to his social background. Therefore, the social equality concept was denied alongside the hard work and equality of chances in achieving The American Dream was denied by the illegal career of Gatsby.